2004
DOI: 10.1097/00004647-200404000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrest/Cardiopulmonary Resuscitation Increases Anxiety-Like Behavior and Decreases Social Interaction

Abstract: SummaryAdvances in medical technology have increased the number of individuals who survive cardiac arrest/ cardiopulmonary resuscitation (CPR). This increased incidence of survival has created a population of patients with behavioral and physiologic impairments. We used temperature manipulations to characterize the contribution of central nervous system damage to behavioral deficits elicited by 8 minutes of cardiac arrest/CPR in a mouse model. Once sensorimotor deficits were resolved, we examined anxiety-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 40 publications
(60 reference statements)
7
49
1
Order By: Relevance
“…Neuronal alterations after CA/CPR augmented the DTH response to pinnae challenge to a subclinical-threshold dose of DNFB (Po0.05; Figure 1). Mice in the CA-normo group showed enhanced edema as compared with mice in the CAhypo group, which were afforded neuronal protection (Neigh et al, 2004b). Neither SHAM surgery (in either temperature condition) nor CA-hypo elicited a DTH response to the subthreshold dose of DNFB, as compared with nonsurgical control mice (P40.05).…”
Section: Delayed Type Hypersensitivity Responsementioning
confidence: 92%
See 4 more Smart Citations
“…Neuronal alterations after CA/CPR augmented the DTH response to pinnae challenge to a subclinical-threshold dose of DNFB (Po0.05; Figure 1). Mice in the CA-normo group showed enhanced edema as compared with mice in the CAhypo group, which were afforded neuronal protection (Neigh et al, 2004b). Neither SHAM surgery (in either temperature condition) nor CA-hypo elicited a DTH response to the subthreshold dose of DNFB, as compared with nonsurgical control mice (P40.05).…”
Section: Delayed Type Hypersensitivity Responsementioning
confidence: 92%
“…A temperature probe was placed in the temporalis muscle on the left side of the head. We have previously shown that cortical temperature and temporalis temperature are highly correlated over a range that encompasses the temperatures experienced during our CA/CPR and SHAM procedures (Neigh et al, 2004b). Thus, temporalis muscle temperature is used as an index of brain temperature.…”
Section: Cardiac Arrest Proceduresmentioning
confidence: 94%
See 3 more Smart Citations